Urinary Tract Infection in Pregnancy and its Correlation with Nitrite Test - Subedi, M; Basnyat, SR; Acharya, SD (Journal of Nepal Health Research Council, 2010)
Background: Urinary Tract Infection is one of the most frequently seen medical complications of pregnant women. The value of screening for bacteriuria by rapid test has to be readdressed considering methods, significance and costs. The study was done to assess the sensitivity and specificity of rapid test (nitrite test) for the confirmation of UTI and etiology of infection during pregnancy and antibiotics sensitivity pattern of the isolates. Methods: In this observational based study, mid stream urine samples from 100 pregnant women clinically suspected of urine infection were evaluated by urine dipstick analysis, microscopic and by culture method. The isolates were identified and antibiotic sensitivity pattern was determined by standard protocol. At the end, Sensitivity, Specificities, Positive and Negative predictive values of isolates were determined from nitrite test. Results: Out of 100 clinically suspected UTI cases, 45% were culture positive of which (55.5%) were Gramnegative bacteria of them Escherichia coli (n=14) was the most common pathogens and Staphyococcus aureus (n=11) was found to be predominant in Gram positive bacteria. Among total 45 positive cases, 17 samples were nitrite positive and also culture positive. The Sensitivity, Specificity, Positive and Negative predictive values of nitrite test in relation to Enterobacteriaceae were 70.8%, 100%, 100% and 91.5% respectively where as Sensitivity, Specificity, Positive and Negative predictive value of nitrite test in relation to Escherichia coli were 100%, 96.6%, 82.3%, and 100%, respectively. Amikacin as well as Gentamycin was found the most effective antibiotics against Gram negative and Gram positive bacteria. Conclusions: Although, confirmatory diagnosis can be achieved by urine culture method, the combination of Nitrite test with pyuria appears to be rapid test and very useful markers for bacterial UTI in district laboratories where culture facilities are rare. On the basis of in vitro tests Amikacin and Ciprofloxacin are comparatively effective drugs for UTI. Key words: antibiotics; nitrite test; pregnant women; urinary tract infection. DOI: 10.3126/jnhrc.v7i2.3011 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 80-83